Group Prenatal Care in Mexico: perspectives and experiences of health personnel - Midiam Ibañez-Cuevas; Ileana Beatriz Heredia-Pi; Evelyn Fuentes-Rivera; Zafiro Andrade-Romo; Jacqueline Alcalde-Rabanal; Lourdes Bravo-Bolaños Cacho; Xochitl Guzmán-Delgado; Laurie Jurkiewicz; Blair G Darney (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: Identify barriers and facilitators to implementing the Group Prenatal Care model in Mexico (GPC) from the health care personnel's perspective. METHODS: We carried out a qualitative descriptive study in four clinics of the Ministry of Health in two states of Mexico (Morelos and Hidalgo) from June 2016 to August 2018. We conducted 11 semi-structured interviews with health care service providers, and we examined their perceptions and experiences during the implementation of the GPC model. We identified the barriers and facilitators for its adoption in two dimensions: a) structural (space, resources, health personnel, patient volume, community) and b) attitudinal (motivation, leadership, acceptability, address problems, work atmosphere and communication). RESULTS: The most relevant barriers reported at the structural level were the availability of physical space in health units and the work overload of health personnel. We identified the difficulty in adopting a less hierarchical relationship during the pregnant women's care at the attitudinal level. The main facilitator at the attitudinal level was the acceptability that providers had of the model. One specific finding for Mexico's implementation context was the resistance to change the doctor-patient relationship; it is difficult to abandon the prevailing hierarchical model and change to a more horizontal relationship with pregnant women. CONCLUSION: Analyzing the GPC model's implementation in Mexico, from the health care personnel's perspective, has revealed barriers and facilitators similar to the experiences in other contexts. Future efforts to adopt the model should focus on timely attention to identified barriers, especially those identified in the attitudinal dimension that can be modified by regular health care personnel training.